Prenatal diagnosis in dermatology - Manjyot Gautam; Faaria Ali (Wolters Kluwer Medknow Publications, 2021)
Prenatal diagnosis (PND) of inherited skin disorders comprises all the diagnostic modalities carried out in utero for couples who are at high risk of producing a child with congenital abnormalities. With the constant research being carried out in the field of molecular diagnosis and genetics, it is of utmost importance for dermatologists to be abreast about all the available means of genetic testing in utero. This will enable us to provide the best of options to the couples who are at risk of having children with inheritable skin disorders so that they can get the tests done at the appropriate time during gestation and the pregnancy can be continued safely till term. This article talks about all the invasive and noninvasive methods of PND practised at present and the ones that may gain popularity in the near future.